Análisis de la distribución espacial de los glaciares rocosos en el Pirineo Central Oscense - Chueca Cia, Javier (Geographicalia, 2017)
One hundred and seventy rock glaciers were identified in un aerial photograph inventory of 6.500 knm2 in the Spanish province of Huesca which includes a major part of the southern Central Pyrenees. The inventory was made on an east-west transect across the province of Huesca between latitudes 42º 19' and 42º 56' north. The study was carried out using statistical techniques (quadrat analysis, Poisson distribution analysis and variance-mean ratio test), and demonstrates the existence of evident irregularities that we have related to differences in lithology and fracturing density over the area studied.